ANALISIS IMPLEMENTASI CORETAX DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK DAN OPTIMALISASI PENERIMAAN NEGARA INDONESIA - Qonitah, Iffah (POLITEKNIK LP3I JAKARTA, 2026)
Taxes are the primary source of state revenue and play a vital role in financing national development. However, the level of taxpayer compliance in Indonesia still faces various challenges, ranging from administrative complexity to limited system transparency. In response, the government, through the Directorate General of Taxes, has implemented Coretax as part of a technology-based tax reform initiative. This study aims to analyze the effectiveness of Coretax implementation in enhancing taxpayer compliance and optimizing state revenue. The research employs a literature review and descriptive analysis using secondary data from official reports, academic publications, and tax policy documents. The findings indicate that Coretax simplifies tax administration processes, strengthens data-driven monitoring, and increases transparency and accountability. Its implementation has contributed positively to improving taxpayer compliance and enhancing revenue efficiency, although challenges remain, particularly related to technological infrastructure readiness, taxpayers’ digital literacy, and the need for capacity building among tax officials. This study underscores the importance of sustaining Coretax development, not only through technological investment but also through strengthened taxpayer education, so that it can serve as a strategic instrument to reinforce Indonesia’s taxation system.